Impact of implementation of sequential trauma education programs (STEPs) course on missed injuries in emergency polytrauma patients, Ismailia, Egypt - Adel Hamed Elbaih; Maged El-Setouhy; Jon Mark Hirshon; Hazem Mohamed El-Hariri; Monira Taha Ismail; Mohamed El-Shinawi (African Journal of Emergency Medicine, 2022)
Introduction: Trauma deaths account for 8% of all deaths in Egypt. Patients with multiple injuries are at high risk but may be saved with a good triage system and a well-trained trauma team in dedicated institutions. The incidence of missed injuries in the Emergency Centre (EC) of Suez Canal University Hospital (SCUH) was found to be 9.0% after applying Advanced Trauma Life Support (ATLS) guidelines. However, this rate is still high compared with many trauma centers. Aim: Improve the quality of management of polytrauma patients by decreasing the incidence of missed injuries by implementing the Sequential Trauma Education Programs (STEPs) course in the EC at SCUH. Methods: This interventional training study was conducted in the SCUH EC that adheres to CONSORT guidelines. The study was conducted during the one month precourse and for 6 months after the implementation of the STEPs course for EC physicians. Overall, 458 polytrauma patients were randomly selected, of which 45 were found to have missed injuries after applying the inclusion and exclusion criteria. We assessed the clinical relevance of these cases for missed injuries before and after the STEPs course. Results: Overall, 45 patients were found to have missed injuries, of which 15 (12%) were pre-STEPs and 30 (9%) were post-STEPs course. The STEPs course significantly increased adherence to vital data recording, but the reduction of missed injuries (3.0%) was not statistically significant in relation to demographic and trauma findings. However, the decrease in missed injuries in the post-STEPs course group was an essential clinically significant finding. Conclusion: STEPs course implementation decreased the incidence of missed injuries in polytrauma patients. Thus, the STEPs course can be considered at the same level of other advanced trauma courses as a training skills program or possibly better in dealing with trauma patients. Repetition of this course by physicians should be mandatory to prevent more missed injuries. Therefore, the validation of STEPs course certification should be completed at least every two years to help decrease the number of missed injuries, especially in low-income countries and low-resource settings.